A taxonomic study on the species of the genus Furcilarnaca (Orthoptera, Gryllacrididae, Gryllacridinae) - Li, Miaomiao; Sun, Mei Ling; Liu, Xianwei; Li, Kai (Zootaxa, 2015)
A taxonomic study of the genus Furcilarnaca Gorochov, 2004 is presented. Four new species are described: F. affinis sp. nov., F. hirta sp. nov., F. fractiflexa sp. nov., F. brachyptera sp. nov.. Two new combinations F. fallax (Liu et al., 2010) comb. nov. and F. pulex (Karny, 1928) comb. nov. are given. A key to the species and the distributional data of Furcilarnaca are provided.